Khasiat Madu bagi Kesehatan Tubuh: Studi Takhrij dan Syarah Hadis - Ahmad Raihan Qolbu Attsani; Hidayatul Fikra; Tamami; Naan (Gunung Djati Conference Series, 2022)
The purpose of this study was to analyze imam Bukhari's hadith number 5684 on the efficacy of honey from the point of view of hadith science. This research uses a qualitative approach that emphasizes the study of literature, by applying takhrij and sharah methods in hadith analysis. Interpretation uses contemporary issue analysis. The results and discussions in this study show that imam Bukhari's hadith number 5684 about honey has a shahih quality according to the takhrij hadith review. While this hadith sharah shows that the Prophet (peace be upon him) advocated the treatment of stomach pain by drinking honey. This is supported by other sharah, namely honey has many properties either for treatment or for regular consumption because it is useful to increase immunity. The conclusion of this study is the hadith of Imam Bukhari number 5684 is considered maqbul (accepted) and can be used as an argument. This study recommends further research collaboration between hadith enthusiasts and medical experts to research the efficacy of honey.